Insights Into the Internal Dynamics of Natural Lahars From Analysis of 3-Component Broadband Seismic Signals at Volcán de Colima, Mexico - Walsh, Braden; Coviello, Velio; Capra, Lucia; Procter, Jonathan; Márquez-Ramirez, Victor (Frontiers in Earth Science, 2020)
Here, we present data from a 3-component broadband seismometer and video camera installed 3 m from the Lumbre channel on Volcán de Colima, Mexico to understand rheology differences within multiple lahar events that occurred in late 2016. We examine differences in frequency and directionality from each seismic component. Results indicate an increase in peak frequency above background in each component when a lahar nears the sensor, and a decrease in overall peak frequency when transitioning from a streamflow to a higher concentration flow. The seismic frequency distribution for the cross-channel component for the streamflow has a wider range compared with the lahar events. In contrast, the peak spectral frequency of the streamflow is narrower in comparison to the lahar events in the flow parallel and vertical directions. Estimated directionality ratios (cross-channel signal divided by flow parallel signal) yielded further evidence for a rheologic change between streamflow and lahars. Directionality ratios >1 were calculated for each lahar, and <1 for streamflow. Finally, we demonstrate from component analyses that channelization or freedom of movement in the cross-channel, bedload transport in the flow parallel, and bed composition in the vertical directions are possibly the main drivers in the peak spectral frequency output of lahars.